IMPLEMENTATION OF PROFESSIONAL ZAKAT FOR STATE CIVIL SERVANTS FROM THE PERSPECTIVE OF MAQASID AL-SHARIA: (Case Study of BAZNAS in Sinjai Regency) - Andi Muh. Taqiyuddin BN; Mukhtar Lutfi; Muammar Muh. Bakry; Rahmawati Muin (Transpublika Publisher, 2023)
The primary focus of this qualitative research is to examine the implementation of professional zakat for Civil Servants (ASN) in Sinjai Regency from the perspective of Maqāṣid Al-Syarī’ah, with BAZNAS as a case study. The research breaks down this central inquiry into specific sub-problems, aiming to analyze the alignment of Maqāṣid Al-Syarī’ah principles with the execution of professional zakat for ASN in Sinjai Regency. Data for the study is primarily sourced from key individuals, including the Chairperson and Vice Chairpersons of BAZNAS in Sinjai Regency, zakat payers, the Head of Zakat and Waqf Implementation at the Ministry of Religious Affairs in Sinjai Regency, the Head of the Regional Finance and Asset Agency, and the Head of the Regional Personnel and Human Resource Development Agency in Sinjai Regency. Data is collected through observation, interviews, and documentation, and the analysis is structured into stages of data collection, reduction, presentation, and conclusion drawing. The research reveals that professional zakat management for ASN by BAZNAS in Sinjai Regency is conducted even without clear local regulations, in coordination with various government entities. The distribution and utilization of zakat adhere to five programs, yet its alignment with Maqāṣid Al-Syarī’ah is hindered by various obstacles in its application for civil servants in Sinjai Regency.